The Description of Egypt from Napoleon to Champollion - Sarfatti, Tamar (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book is the first study in English of the multi-volume set of texts and engravings of the Description of Egypt, a work produced following the three-year-long Egyptian campaign led by Napoleon Bonaparte in 1798. The book challenges the conventional and rather reductive interpretation of the Description that followed Edward Said's Orientalism, as a summation of an orientalist colonial project. It re-centres the Description in the much more complex and dynamic political and intellectual world of France of the late eighteenth and early nineteenth century and its colonial aspirations. It follows closely the notes, texts, and illustrations of the contributors to the work, the majority of whom were graduates of the first years of the Polytechnic school in Paris, and the well-documented editing process that continued for almost thirty years, in which France moved from Revolution to Empire and Restoration. It shows the ways in which scholarly traditions and newly acquired skills interplay with Enlightenment texts, contemporary politics, and received ideas about antiquity, and how these were reinterpreted and modified - in texts and illustrations - through the encounter with the physical and social worlds of Ottoman Egypt. Using the rich repository of the Description of Egypt the book demonstrates the contribution of antiquarian methods of research to the emerging disciplines of the social sciences. Tamar Sarfatti is an independent scholar, based in the UK and Israel.
1. Introduction -- 2. An Eighteenth-Century Common Reader: Napoleon Bonaparte -- 3. Colonial Policies and Revolutionary Ideas -- 4. A Short History of the Making of the Description of Egypt -- 5. Literary Genres and Scholarly Traditions -- 6. Engineer Training in Eighteenth-Century France: "From the World of More or Less to the Universe of Precision" -- 7. Egypt Engraved -- 8. Texts About Ancient Egypt and Their Predecessors -- 9. Describing Modern Egyptian Society -- 10. Jomard and Champollion: A Rivalry at the Birth of Egyptology -- 11. Conclusion.
Keywords: France-History.; Middle East-History.; Imperialism; Civilization-History.; Books-History.; History of France; History of the Middle East; Imperialism and Colonialism; Cultural History; History of the Book